Associations Between Acculturation, Discrimination, and Adolescent Relationship Abuse: A Matched Parent-Adolescent Study of Latine Families - Huerta, Christina (Journal of interpersonal violence, 2025)
Adolescent relationship abuse (ARA) is prevalent among adolescents, including those who identify as Latine. However, there is limited research that has considered the cultural and structural mechanisms that may impact ARA experiences among Latine youth. Further, although parents play a crucial role in ARA prevention, few studies have investigated how adolescent-parent differences in acculturation and discrimination are associated with ARA. The objective of this exploratory study of Latine families was to examine how acculturation, discrimination, and adolescent-parent acculturation/discrimination differences relate to ARA victimization and perpetration. Parent-adolescent dyads recruited from clinic and community-based settings in Pittsburgh and Kansas City completed matched surveys. Parent-adolescent acculturation and discrimination differences were calculated using multilevel linear models. Multivariable logistic regression was used to examine associations among ARA victimization and perpetration and adolescent-reported acculturation, adolescent-reported discrimination, and adolescent-parent acculturation and discrimination differences. One hundred eighty-two adolescents and their parent/caregiver (n = 364) completed a matched survey in English or Spanish from March 2020 to March 2021. Forty-three percent of adolescents reported that they had started dating; of these 35% and 24% reported ARA victimization and perpetration, respectively. Higher levels of adolescent-reported acculturation conflict were associated with lower ARA victimization (adjusted odds ratio [aOR]: 0.24; 95% confidence interval, CI [0.08, 0.75]); conversely, higher adolescent-reported discrimination was associated with ARA victimization (aOR: 2.50 [1.30, 4.60]) and perpetration (aOR: 2.10 [1.10, 3.90]). Wider adolescent-parent acculturation differences in Spanish language (aOR: 3.40 [1.04, 11.30]) and interpersonal discrimination (aOR: 2.40 [1.10, 5.20]) were associated with increased ARA victimization. Results underscore the importance of discrimination in understanding ARA experiences among Latine youth. Future work should consider developing culturally and linguistically affirming ARA prevention programs for Latine adolescents and parents.